PERAN KOMUNITAS DALAM PENANGANAN TEMUAN BARU PRASASTI (STUDI KASUS KOMUNITAS KANDANG KEBO) - Goenawan A. Sambodo; Maria Tri Widayati; Hery S. Purnawali (Balai Arkeologi Yogyakarta, 2019)
The aim of this study is to identify and analyze the efforts of the Kandang Kebo Community in handling new found inscriptions. The method used is descriptive-qualitative, combined with inductive reasoning. Structural analytic, especially Internal Criticism (transliteration, translation and interpretation) is also applied to analyse the new found inscription. Information for this study were collected from the members of Kandang Kebo community, stakeholders, and local community. Data collection were done by observation, literature study, interviews, and documentation. This study found that community which participate in maintaining cultural heritage objects is a provision in the Cultural Heritage Act no. 11 of 2010. Kandang Kebo as a society's community has been trying to apply this Act. The using of social media becomes one of the methods, with its quick and easy way; it makes new artifacts discovery easier to be known by others. Kandang Kebo then proceed this news to the office of BPCB. There are some inscriptions that are successfully saved and read by Kandang Kebo, followed by positive responses from the government.